2017
DOI: 10.1287/opre.2016.1575
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Award Scheme in Innovation Tournaments

Abstract: In an innovation tournament, an organizer solicits innovative ideas from a number of independent agents. Agents exert effort to develop their solutions, but their outcomes are unknown due to technical uncertainty and/or subjective evaluation criteria. To incentivize agents to make their best effort, the organizer needs to devise a proper award scheme. While extant literature either assumes a winner-take-all scheme a priori or shows its optimality under specific distributions for uncertainty, this paper derives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(26 citation statements)
references
References 16 publications
(28 reference statements)
2
23
0
Order By: Relevance
“…An implication here is that firms with a larger number of employees (resulting in a larger solver pool) will be instituting a smaller reward as they can leverage the greater chances of obtaining an extreme value solution arising purely from the order statistic effect. Our result here is consistent with the results obtained by Ales et al (2017) in their analysis of an "external" contest.…”
Section: Production and Operations Managementsupporting
confidence: 93%
See 1 more Smart Citation
“…An implication here is that firms with a larger number of employees (resulting in a larger solver pool) will be instituting a smaller reward as they can leverage the greater chances of obtaining an extreme value solution arising purely from the order statistic effect. Our result here is consistent with the results obtained by Ales et al (2017) in their analysis of an "external" contest.…”
Section: Production and Operations Managementsupporting
confidence: 93%
“…Further work showed that in cases associated with large uncertainty in the contest outcome, unrestricted entry is optimal as it increases the chances of obtaining an extreme value solution (Boudreau et al, 2011;Körpeoglu & Cho, 2018;Terwiesch & Xu, 2008). Other contest work examined the relationship of the number of participants with the reward structure (Ales et al, 2017;Azmat & Möller, 2009;Moldovanu & Sela, 2001;Stouras et al, 2021), output uncertainty (Ales et al, 2017(Ales et al, , 2021 and contest duration (Chen et al, 2021). Bockstedt et al (2016) study contests where submissions are public and observe that inspite of intellectual property loss considerations, contestants that submit earlier are more likely to win the contest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2016), feedback mechanism (Mihm and Schlapp 2018, Wooten and Ulrich 2017), and incentive and award structure (Ales et al. 2017, 2018a, Erat and Krishnan 2012, Körpeoğlu and Cho 2018); see Ales et al. (2018b) for a more comprehensive review for this literature.…”
Section: Inclusive Innovation: An Operations Lensmentioning
confidence: 99%
“…This arises from the fact that such innovation contests are organized by the clients (e.g., firms) who can determine the format of contest; cf. Ales et al (2017), and the projects are highly intellectually demanding (e.g., programming or algorithm development) with the success rate mainly depending on the effort invested by contestants. By comparison to this stream of literature, we study contest-based crowdsourcing from a different perspective by considering multiple projects with relatively simple fixed rules decided by the platforms.…”
Section: Existing Studies On Crowdsourcing Problemsmentioning
confidence: 99%